«Вызов и ответ»: перспективы исторической науки в начале нового тысячелетия - Репина, Л. (Інститут історії України НАН України, 2008)
The article deals primarily with the recent changes in the spheres of historical consciousness, historical epistemology, in t he conceptions of historical understanding and the estimation of the cognitive potential of historical science. The author analyzes the most interesting attempts to create new theoretical models aiming to restore the integrity of historical vision of the past in the new interdiscipl inary context. The author concludes that the long search for new synthesizing paradigm has resulted in elaboration of conceptions of historical development grouping around di fferent versions of “theories of practice” and integral theoretical model based on combination of m icro- and macrohistorical analysis. The neoclassical paradigm orientate itself on the study of both culture as a set of norms and values and the mode of its “work” in the specific social context.